A LOOK TO THE INFRASTRUCTURE DIMENSION AS ONE OF THE OBJECTIVE CONDITIONS ENABLERS OF QUALITY IN PUBLIC SCHOOLS - Padua Sabia, Claudia Pereira de [UNESP]; Lemes de Sordi, Mara Regina (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2021)
External evaluations and their indicators have unilaterally made the school and its professionals responsible for the results achieved by students, disregarding the weight of objective conditions for the development of school work, which affects the self-esteem of teachers and administrators. The aim of this study is to identify and analyze the objective conditions of public elementary schools from a teaching board with emphasis on the infrastructure dimension. To this end, the methodology used involves a quantiqualitative approach and combines bibliographic research, document analysis and application of questionnaires. The data collection consisted of a google docs questionnaire sent to teachers in the final years of elementary school from a teaching directorate in the west of Sao Paulo. As a result, we identified that of the 47 schools surveyed, 22 (46.80%) have elementary infrastructure, 24 (51.06%) can be classified as basic infrastructure, none adequate, none advanced that would be the highest level of the infrastructure scale proposed by Soares Neto, Jesus, Karino and Andrade; (2013). The indicators of the infrastructure dimension show that the objective conditions are predominantly precarious, which compromises the development of teaching work. However, the objective conditions are underestimated in the evaluation processes that blame only one of the poles, that is, the school and its professionals for the results of external evaluations and does not hold the State responsible for not offering them. We consider the need to discuss the evaluation results in the perspective of shared, that is, participatory, accountability, in which the public power recognizes itself in the quality improvement process, assuming its part.
Keywords: School quality; Objective conditions; School infrastructure; Participatory educational accountability; External evaluation; Participatory Institutional Assessment (AIP)